Factors associated with glycemic status among type 2 diabetes mellitus patients in Merjan Diabetic Centre, Iraq - Al Hasnawi, Ali Kadhim Abbood (2015)
Type 2 diabetes mellitus (DM) is now posing the largest disease threat to Iraq’s health care services with the majority of those patients was reported to have a poor glycemic status. Role of nutrition therapy is important; however, their nutritional status is not being fully addressed. Therefore, this cross sectional study aimed to determine nutritional status-related factors and their contribution to glycemic status in a sample of Iraqi patients. Patients with T2 DM were recruited as a convenience sample from Merjan Diabetic Centre in Iraq, and participated in this study. Nutritional status characteristics namely anthropometric, biochemical, clinical and dietary intake data including calculated dietary Glycemic Index (GI) and Glycemic Load (GL) were collected. Glycemic status was assessed using the HbA1c level. Medical characteristic and other lifestyle behaviours, including smoking status and physical activity level were also obtained. Factors contributed to glycemic status were determined using multiple linear regression analyses. A total of 170 diabetic patients (91 males, 79 females), aged 20 to 70 years (51.2 ± 10.2 years) were recruited with a response rate of 91%. In this study, mean HbA1c of the patients was 10.4 ± 1.6% with only 0.6% achieved the target treatment goal of HbA1c < 7%. About 45% and 44.2% of the subjects were overweight and obese respectively. Average daily energy intake of the patients was 2032.7 ± 274.6 kcal with the proportion of macronutrients were in line with the professional bodies’recommendation. There were seven factors namely; patients who were on diet alone (β= 0.25, t = 3.949, p = 0.0001); LDL level (β= -0.331, t = 5.388, p = 0.0001); dietary GL (β = 0.162 , t = 2.714, p = 0.007); physical activity level (β= -0.241 , t = -3.580, p =0.0001); BMI (β= 0.214 , t = 3.395, p = 0.001); patients who were on Sulfonylurea (β =-0.167, t = -2.615, p = 0.01); total fiber (β = 0.133, t = -2.169, p = 0.032); were found to be the predictors which has been explained about 45% of the variation (R2 = 0.45) in glycemic status. In conclusion, the present study showed the significant contribution of diet alone, LDL level, Dietary GL, Physical activity, BMI, Sulfonylurea and total dietary fibre to glycemic status. Future studies should consider incorporating these components into the model to increase the effectiveness of any intervention to Iraqi type 2 DM.